Participação, reflexão crítica e movimento no processo avaliativo do SINAES: entrevistas com membros de comissões próprias de avaliação sobre a auto-avaliação institucional - Retz, Raquel de Godoy (2007)
The purpose of this study is to investigate how the aspects of participation, critical consideration and movement occur in the self-evaluation process, according to the proposal of the national system for college evaluation (SINAES). This system was legally established in 2004. Since then, SINAES has been motivating the selfevaluation and establishing a relationship between the self-evaluation with the control area system. In the revision of the concepts related to the Institutional evaluation and in the SINAES rules, the classes of participation, critical consideration and movement were highlighted as significant. Interview was used as a methodology. Five members from the specific group of evaluation (CPA) were chosen from five distinct college institutions (IES). The member chosen was the one that had participated in the self-evaluation process in their respective IES. The data analysis indicated a few difficult of the institutions related to the organization and motivation in the participation of their members, less critical consideration on the IES data and almost any movement encouraged by the selfevaluation. It is also noticed the CPA effort for the successful of self-evaluation, and for the institutions to develop their own evaluation culture. As a result, it is expected that, from the institution evaluation, the institutions improve their quality